The Relative Accuracy of Different Methods for Measuring Mind Wandering Subtypes: A Systematic Review - Sholeh Nazari; Paul Fitzgerald; Reza Kazemi (Brain and Behavior)
ABSTRACT Purpose Mind wandering, the shift of attention from a primary task to unrelated thoughts, is a pervasive cognitive phenomenon with significant implications for cognition, emotion, and behavior. Despite its prevalence, accurately measuring mind wandering and its subtypes remains a challenge due to its subjective and dynamic nature. Method This systematic review evaluated the strengths and limitations of methods for measuring mind wandering subtypes, synthesizing findings from 555 studies. Questionnaires and experience sampling methods (ESMs) were most frequently used, offering high ecological validity but limited by self‐report biases. Neuroimaging techniques, such as fMRI and EEG, provided objective insights into neural correlates, particularly the default mode network (DMN), but were constrained by high costs and low ecological validity. Behavioral tasks revealed task‐related attentional lapses but lacked sensitivity to spontaneous mind wandering, while physiological measures and eye‐tracking offered unique perspectives but required complex data analysis. Finding To address the challenges associated with the limitations of existing methodologies for assessing mind wandering, we propose the Multidimensional Assessment of Mind Wandering (MAMW) framework, which integrates diverse methodologies to provide a comprehensive understanding of mind wandering. Conclusion The findings highlight the need for standardized measurement tools, greater ecological validity, and longitudinal research to explore the developmental and clinical trajectories of mind wandering. Future studies should prioritize integrating multiple methods to advance both theoretical knowledge and practical applications in clinical, educational, and workplace settings.